Novel Bruton's Tyrosine Kinase inhibitor remibrutinib: Drug‐drug interaction potential as a victim of CYP3A4 inhibitors based on clinical data and PBPK modeling. Issue 1 (25th August 2021) - Huth, Felix; Schiller, Hilmar; Jin, Yi; Poller, Birk; Schuhler, Carole; Weis, Wendy; Woessner, Ralph; Drollmann, Anton; End, Peter
Abstract: Remibrutinib, a novel oral Bruton's Tyrosine Kinase inhibitor (BTKi) is highly selective for BTK, potentially mitigating the side effects of other BTKis. Enzyme phenotyping identified CYP3A4 to be the predominant elimination pathway of remibrutinib. The impact of concomitant treatment with CYP3A4 inhibitors, grapefruit juice and ritonavir (RTV), was investigated in this study in combination with an intravenous microtracer approach. Pharmacokinetic (PK) parameters, including the fraction absorbed, the fractions escaping intestinal and hepatic first‐pass metabolism, the absolute bioavailability, systemic clearance, volume of distribution at steady‐state, and the fraction metabolized via CYP3A4 were evaluated. Oral remibrutinib exposure increased in the presence of RTV 4.27‐fold, suggesting that remibrutinib is not a sensitive CYP3A4 substrate. The rich PK dataset supported the building of a robust physiologically‐based pharmacokinetic (PBPK) model, which well‐described the therapeutic dose range of 25–100 mg. Simulations of untested scenarios revealed an absence of drug‐drug interaction (DDI) risk between remibrutinib and the weak CYP3A4 inhibitor fluvoxamine (area under the concentration‐time curve ratio [AUCR] <1.25), and a moderate effect with the CYP3A4 inhibitor erythromycin (AUCR: 2.71). Predictions with the moderate and strong CYP3A4 inducers efavirenz and rifampicin, suggested a distinct remibrutinib exposure decrease of 64% and 89%. Oral bioavailability of remibrutinib was 34%. The inclusion of an intravenous microtracer allowed the determination of all relevant remibrutinib PK parameters, which facilitated construction of the PBPK model. This will provide guidance on the selection or restriction of comedications and prediction of DDI risks.